MENCARI FORMAT LAPORAN KEUANGAN YANG SESUAI DENGAN KLUB SEPAK BOLA DI INDONESIA: STUDI KASUS PADA KLUB SEPAK BOLA PERSEMA - Siddik, Muhammad Hananto; Chariri, Anis (Diponegoro Journal of Accounting, 2013)
This study aimed to find out the format of financial statement presentation appropriate for football clubs in Indonesia. This study seeks to analyze how the financial reports generated by the football club in Indonesia is able to provide quality information for the interested parties to fulfill the accountability aspect. This research was conducted with qualitative methods through a case study on the football club Persema by interviewing the CEO of PT. Singosari Sakti Indonesia and financial staff, as well as analysis of financial statements and related documents obtained directly from the company. In this research, analysis of financial statements Arsenal and Juventus is employed as a benchmark of financial statements presentation. Therefore, this study also provide an advice as a reference about the form of financial statements in accordance format for a football club in Indonesia that will be go public in the future. The suggestions are given on the basis of IFRS standards and compliance aspects of accountability against AFC.